Application of The Wakalah Bil Ujrah Wa Tabarru Agreement at Pt. Takaful Public Branch Padang Insurance - Indra, Novalia; Johanna, Anne; Avinash, Buschhaus (Journal International Dakwah and Communication, 2021)
The main problem in this thesis is "How to Apply Wakalah Bil Ujrah Wa Tabarru" at pt. Field branch general takaful insurance with Problem Limitations How to apply the concept of wakalah bil ujrah was tabarru 'contract at PT. Padang Branch General Takaful Insurance, What is the form of premium management in the wakalah bil ujrah wa tabarru ' contract at PT. Padang Branch General Takaful Insurance, and How to resolve the obstacles that occur in the wakalah bil umrah was tabarru's contract. The purpose of this research is to determine the implementation of Wakalah Bil Ujrah Wa Tabarru 'Contract at PT. Padang Branch General Takaful Insurance The purpose of this research is to describe and describe to the public the wakalah bil umrah was a tabarru contract. To develop knowledge through the Study Program that the author is diligent in, to increase the author's knowledge and insight, as input for the Padang Branch General Takaful Insurance and the community as participants in the Padang Branch General Takaful Insurance. And as one of the requirements to obtain a bachelor's degree in Islamic economic law in the Islamic economic law study program majoring in sharia at the Batusangkar State Islamic Religious High School.